Application of bacterial nanocellulose-based wound dressings in the management of thermal injuries: experience in 92 children - Maurer, Kristina; Renkert-Baudis, Miriam; Duis, Malte; Weiß, Christel; Wessel, Lucas; Lange, Bettina (Burns, 2022)
Background - Management of pediatric thermal injuries involves a high standard of care in a multidisciplinary setting. To avoid physical and psychological sequelae, wound dressings should minimize hospitalization time and anesthesia while maximizing patient comfort. - Patients and methods - 190 children with thermal injuries of the torso, arms and legs were treated with polyurethane foam dressings or bacterial nanocellulose sheets. Data were analyzed retrospectively regarding hospitalization, procedures with general anesthesia, scar formation, rate of infection and need for skin grafting. - Results - The groups did not differ significantly concerning age, gender distribution or percentage of injured total body surface area. Statistical analysis showed that length of hospitalized care and procedures undergoing anesthesia were significantly reduced in the nanocellulose group (each p < 0.0001). There was no significant difference in rate of complications, wound healing and rate of skin grafting between the two subgroups. - Discussion - Acting as a temporary epidermal substitute, bacterial nanocellulose enables undisturbed reepithelialization without further wound dressing changes. In children, no additional topical antimicrobial agents are indicated for unimpaired wound healing. - Conclusions - Bacterial nanocellulose is superior to polyurethane foam regarding length of hospitalization and number of interventions under anesthesia. It offers a safe, cost-effective treatment option and provides excellent comfort in pediatric patients.